Penerapan Penyembelihan Hewan Ditinjau Menurut Mazhab Imam Syafi’ : (Studi Kasus Penyembelihan Hewan Qurban Mas Hendro Kec. Gebang Kab. Langkat) - Rahmat Prawira, Azhar, Suaib Lubis (Mediation : Journal Of Law, 2022)
The problems found at the research location were: The community's understanding of the slaughter of sacrificial animals in accordance with the provisions of the Shari'a was not optimal, specifically in the process of slaughtering and managing qurban meat. Communities that carry out qurban animal slaughter still use conventional techniques, namely slaughtering qurban animals, namely they have not paid attention to government recommendations and instructions regarding the slaughter of qurban animals by paying attention to health and biological aspects. Based on the results of these observations, the researchers used qualitative research techniques by collecting data through observation and interviews. As for the research results that can be concluded by researchers, namely the application of sacrificial animal slaughter in Air Hitam Village, Kec. Gebang is in accordance with Islamic law, namely by following the slaughtering procedures in accordance with Islamic rules and law.